2006
DOI: 10.1016/j.neuron.2006.04.005
|View full text |Cite
|
Sign up to set email alerts
|

SALM Synaptic Cell Adhesion-like Molecules Regulate the Differentiation of Excitatory Synapses

Abstract: Synaptic cell adhesion molecules (CAMs) are known to play key roles in various aspects of synaptic structures and functions, including early differentiation, maintenance, and plasticity. We herein report the identification of a family of cell adhesion-like molecules termed SALM that interacts with the abundant postsynaptic density (PSD) protein PSD-95. SALM2, a SALM isoform, distributes to excitatory, but not inhibitory, synaptic sites. Overexpression of SALM2 increases the number of excitatory synapses and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
193
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 140 publications
(202 citation statements)
references
References 58 publications
(100 reference statements)
7
193
2
Order By: Relevance
“…Synaptic adhesion-like molecules (SALMs) 2 are a recently identified class of adhesion molecules that are highly enriched in brain (11)(12)(13). All five members of the SALM family contain extracellular leucine-rich repeats (LRR), an immunoglobulin C2-like (IgC2) domain, a fibronectin type III (FNIII) domain, a transmembrane domain, and a cytoplasmic C-terminal tail.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Synaptic adhesion-like molecules (SALMs) 2 are a recently identified class of adhesion molecules that are highly enriched in brain (11)(12)(13). All five members of the SALM family contain extracellular leucine-rich repeats (LRR), an immunoglobulin C2-like (IgC2) domain, a fibronectin type III (FNIII) domain, a transmembrane domain, and a cytoplasmic C-terminal tail.…”
mentioning
confidence: 99%
“…All five members of the SALM family contain extracellular leucine-rich repeats (LRR), an immunoglobulin C2-like (IgC2) domain, a fibronectin type III (FNIII) domain, a transmembrane domain, and a cytoplasmic C-terminal tail. SALMs 1-3 contain a C-terminal PDZ-binding domain (PDZ-BD), which associates with the PSD-95 family of proteins (11)(12)(13). SALMs are expressed early in the developing nervous system and persist into adulthood.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Among the factors that regulate the development of neural circuits, proteins containing extracellular leucine-rich repeat (LRR) domains have recently emerged as key organizers of connectivity (de Wit et al, 2011;Ko and Kim, 2007). Artificial synapse formation assays have shown that a host of LRR-containing proteins, which are widely and highly expressed in the brain, are capable of recruiting various synaptic scaffolds and inducing synaptic differentiation in heterologous cells in which these LRR-containing proteins are exogenously expressed (de Wit et al, 2009;Kim et al, 2006;Ko et al, 2006;Linhoff et al, 2009;Mah et al, 2010;Takahashi et al, 2011;Woo et al, 2009). Selected LRR proteins that function at synapses are shown in Fig.…”
Section: Introductionmentioning
confidence: 99%